2010
DOI: 10.1093/ntr/ntq068
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and metabolites in meconium as evidence of maternal cigarette smoking during pregnancy and predictors of neonatal growth deficits

Abstract: Introduction: Many women continue tobacco use during pregnancy despite known adverse consequences on neonatal growth and development. Testing meconium, the first neonatal feces, for tobacco biomarkers offers objective evidence of prenatal tobacco exposure. However, relationships between the amount, frequency, and timing of cigarette smoking during gestation and tobacco biomarker meconium concentrations and neonatal outcomes are unclear.Methods: Eighty-seven pregnant women provided detailed self-reports of dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
3
48
2
Order By: Relevance
“…For instance, in a meta-analysis of studies on SHS exposure during pregnancy, Leonardi-Bee, Smyth, Britton, and Coleman (2008) reported a significant association between SHS exposure and low birth weight at term and small for gestational age status among nonsmoking mothers. Other studies have noted similar results with lower fetal biometry at 20-24 weeks gestation (Hanke, Sobala, and Kalinka, 2004), higher risk for fetal death, preterm delivery, and low birth weight (Gray et al, 2010;Jaddoe et al, 2008). SHS exposure during pregnancy has also been associated with poorer respiratory health among infants over the first 6 months of life (Jedrychowski et al, 2007), and among children with asthma, higher exposure to SHS is associated with higher externalizing behavior problems in the early school years (Yolton et al, 2008).…”
mentioning
confidence: 68%
“…For instance, in a meta-analysis of studies on SHS exposure during pregnancy, Leonardi-Bee, Smyth, Britton, and Coleman (2008) reported a significant association between SHS exposure and low birth weight at term and small for gestational age status among nonsmoking mothers. Other studies have noted similar results with lower fetal biometry at 20-24 weeks gestation (Hanke, Sobala, and Kalinka, 2004), higher risk for fetal death, preterm delivery, and low birth weight (Gray et al, 2010;Jaddoe et al, 2008). SHS exposure during pregnancy has also been associated with poorer respiratory health among infants over the first 6 months of life (Jedrychowski et al, 2007), and among children with asthma, higher exposure to SHS is associated with higher externalizing behavior problems in the early school years (Yolton et al, 2008).…”
mentioning
confidence: 68%
“…Previous research indicated that a positive infant meconium sample refl ects primarily third trimester exposure (Gray et al, 2010a(Gray et al, , 2010b. All infants with positive meconium samples had mothers who smoked in at least the fi rst trimester.…”
Section: Methodsmentioning
confidence: 94%
“…Meconium specimens were assayed with a validated LS-MSMS method for nicotine, cotinine, and trans-3'-hydroxycotinine (Gray et al, 2010a(Gray et al, , 2010b. Among the 189 pregnant smokers, 96% self-reported smoking during pregnancy; 59% had infants with nicotine and/or metabolites in meconium; and 79% had oral fl uid samples that tested positive for cotinine, a primary metabolite of nicotine.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies (i.e., Gray et al, 2010;Kallen, 2000) that investigated effects of MSDP on fetal and infant head circumference were not included in this review as results have been highly consistent (MSDP associated with decreased fetal and infant head circumference) and because the studies do not provide insight into specific structural or functional alterations of the brain.…”
Section: Methodsmentioning
confidence: 99%